The Successful Academic Journal: Manual for Editors and Publishers [In Bulgarian] - B.V. Toshev (University of Sofia, 2012)
The successful academic journals mark the development of the scientific areas in correspondence with their profiles. These journals after inspection are included in the world system for indexing, abstracting and evaluation. Outside of this system are the marginal journals. The present paper advocates the presentation of the academic journals in the prestige secondary scientific sources; it comments the international requirements that should be covered successfully in order such an inclusion to be realized.